Effects of Highly Bioavailable Curcumin Supplementation on Common Cold Symptoms and Immune and Inflammatory Functions in Healthy Japanese Subjects: A Randomized Controlled Study. - Yoshitaka Kuwabara; Akiko Hirose; Hyunjin Lee; Toshihiro Kakinuma; Asami Baba; Tsuyoshi Takara (Journal of Dietary Supplements, 2024)
This study aimed to investigate the effects of 12-week consumption of highly bioavailable curcumin (150 mg/day of Theracurmin Super [TS -P1] or Theracurmin [CR-033P]) on common cold symptoms, immune function, and inflammatory markers. A randomized, double-blind, placebo-controlled study was conducted from November 2021 to May 2022 on 99 healthy Japanese adults. Using a computerized random number generator, each subject was randomly assigned to one of the following three groups: TS -P1, CR-033P, or placebo (n = 33 per group). For 12 weeks, each group consumed the four capsules that were given to them daily. The cumulative number of days for which common cold symptoms persisted was set as the primary outcome. Immunity parameters, inflammatory parameters, liver function parameters, and physical examination results were additional outcomes. A safety assessment was also performed. Ninety-four subjects completed the study, and the per protocol set included 30 subjects in the placebo group, 32 subjects in the TS -P1 group, and 33 subjects in the CR-033P group. The cumulative number of days for which common cold symptoms persisted was significantly lower in the TS -P1 and CR-033P groups than that in the placebo group. No adverse effects were observed. Consumption of highly bioavailable curcumin, TS -P1 or CR-033P (150 mg/day), for 12 weeks reduced the number of days for which common cold symptoms persisted in healthy Japanese adults.